Assessment of acid phosphatase enzyme and influence of potassium iodide on its production in the yeast form of Sporothrix schenckii - Bareja, Rajesh; Grover, Prem S.; Mehra, Sudhir K. (International Journal of Research in Medical Sciences, 2019)
Background: Sporotrichosis is caused by a dimorphic fungal species, Sporothrix schenckii (S. schenckii). The enzyme acid phosphatase is pervasive among yeast and yeast like fungi. It has been studied in various fungi like Aspergillus oryzae, Candida albicans etc. but in S. schenckii little is known about enzyme acid phosphatase. The present study depicts the in-vitro influence of Potassium Iodide (KI) on the enzyme acid phosphatase produced by the S. schenckii (yeast form). Methods: A master culture was prepared by incorporating the standard strain of S. schenckii in YNB (Yeast Nitrogen Base) medium and was incubated at 37ºC. After preparing the increasing concentrations with KI in YNB medium, 1.0 mL suspension of master culture was inoculated into each bottle and incubated at 37ºC for different time period 6th, 12th, 18th day (early, mid, peak of log period) respectively. After centrifuging, a 5% homogenate was prepared, which was used for acid phosphatase enzyme assay. Results: The mean acid phosphatase level of control specimen was 20.9±2.01, 50.0±2.25, 45.0±5.10 μg and test specimens was ranged from 14.9±4.89 to 20.2±3.49, 10.2±4.19 to 40.0±6.39 and 10.0±1.81 to 34.7±6.08 μg on day 6, 12 and 18 respectively. The mean value was lower significantly for all the test concentrations as compared to control (p<0.05). Conclusions: The low activity of the enzyme acid phosphatase indicates that KI has inhibitory effect on the growth of S. schenckii that has led to decrease in the activity of the enzyme.